Protective antibody titre against Newcastle disease in ostriches (Struthio camelus) - Darminto .; Sjamsul Bahri; N. Suryana (Indonesian Center for Animal Research and Development (ICARD), 1998)
The aim of this study was to define an estimated antibody titre which was considered to be protective against Newcastle disease (ND) virus infection in ostriches. Eighteen young ostriches of 4 days of age were divided into two groups each containing 9 birds. The first group was unvaccinated and the second group was vaccinated against ND virus twice at 4 and 14 days of age. Antibody titres were monitored at 1, 14, 28, 42, 56, 70 and 85 days of age by haemagglutination inhibition (HI) test. All birds were then challenged with a velogenic strain of ND virus, Ita strain, at 42 days of age. The excretion of the challenge virus were monitored daily after challenge up to the end of this experiment. Several organs such as brain, trachea, lungs and spleen were collected from died birds for re-isolation of the challenged virus. Results indicated that all unvaccinated birds succumbed to the challenged virus, except one bird that survived challenged. In contrast to the unvaccinated birds, all vaccinated birds survived challenged, except two birds with low antibody titres succumbed challenged. All birds with antibody titres of 4 (HI-log2) or greater survived challenged. All challenged birds excreted the challenged virus through out their oropharyngs. Moreover, challenged virus can be successfully re-isolated from most organs of the died birds. This study concludes that : (a) the estimated protective titre against ND in ostriches is 4 (HI-log2), (b) the immune status for ostrich with antibody titre less the 4 (HI-log2) could not be defined, and (c) vaccination against Newcastle disease in ostriches could successfully prevent birds from sick and died of ND, but unable to prevent virus infection and unable to stop carrier status after infection. Key words : Newcastle disease, ostrich, antibody, protective titre